Meneguhkan NKRI di Madura (Studi Atas Peran Pesantren dalam Membendung Radikalisme di Madura) - Munif Munif (Institut Ilmu Keislaman Annuqayah, 2016)
Maintaining the integrity of The Republic of Indonesia (NKRI) from a variety of threats is the responsibility of all parties in this country, including Pesantren (Islamic boarding schools) as the oldest educational institutions in Indonesia. Madura, as the islands are well known as the island of a thousand pesantrens, it has big role in maintaining the integrity of the Republic of Indonesia. There are four pesantrens in Madura that is thorough in applying their tactical role in maintaining this country from the threat of radicalization that has been threatening the integrity of the Republic of Indonesia in Madura. They are PP Nurul Amanah Bangkalan, PP Darul Ulum Sampang, PP Riyadhus Shalihin Pamekasan and PP Guluk Annuqayah Guluk-guluk Sumenep. This study found that the four have role in actively stemming the radicalization in Madura if only culturally, not specifically and tactically. Pesantren can be used as an effective media to reinforce the pillars of The Republic of Indonesia. Moreover, when this country face the threat of radical Islamic groups. Indeed, these pesantrens do not have a strategy that specifically seeks to face with the movement of radical Islamic groups. However, their activities show their efforts to strengthen the integrity of the Republic of Indonesia in facing the threat of religious radicalization. For example, by strengthening Islam as rahmatan lil’a>lami>n through study groups by the priest, encouragement to the people to make the law of State as the foundation of life, and so on.